Bibliotecas y derechos de autor: análisis comparativo de la nueva legislación de España y Portugal - Fernández Molina, Juan Carlos (2008)
Digital technology has transformed the ways and methods to create and disseminate intellectual works and, in consequence, the ways in which libraries make them available to their users. These technological changes have, of course, directly affected the legislation on copyright, which has undergone successive modifications in recent years both at the international and national level, including the limitations and exceptions to the rights that benefit libraries in their ability to accomplish their aims. This paper carries out a comparative analysis of new scenario for the library privileges in the copyright laws of Portugal and Spain, both recently renovated